Gastrıc cancer surgery in elderly patients: promising results from a mid-western population - YEGEN, ŞEVKET CUMHUR (My University, 2023)
Backgrounds: Extended resection for gastric cancer in elderly patients is still challenging for surgeons. This study aimed to evaluate the prognosis and the postoperative outcomes of elderly patients underwent gastric cancer surgery in a high-volume center. Methods: The medical records of patients with gastric cancer surgery at Marmara University Hospital’s General Surgery Department were examined retrospectively. Patients were divided into two groups: Age ≤ 70 and Age > 70. The clinicopathological data of the patients were compared. The prognostic factors regarding gastric cancer surgery were analyzed with Cox proportional regression models. Kaplan Meier analysis and log-rank test were used to compare Overall Survival (OS) and Cancer-Specific Survival (CSS) among the groups. Competing risk regression analysis was used to examine cause-specific hazards among elderly patients. Results: The number of eligible patients was 250. Age > 70 group was 68 patients, and Age ≤ 70 group was 182 patients. There is no significant difference between the patient’s demographics or pathological outcomes. Neoadjuvant therapies performed less in elderly patients [40 (22%) vs. 7 (10%), p: 0.03, respectively]. There was no significant difference in severe complication (≥ Grade III) rates in both groups. Multivariate analysis showed that advanced T stage and adjacent organ invasion were the independent risk factors for OS. No significant difference was observed between the groups regarding OS (Log Rank (Mantel-Cox): 0.102). Younger patients have worse CSS than those who are older. Cause-specific hazard model demonstrated a not increased hazard ratio [HR: 1.04(0.78–1.38)] for elderly patients for OS and CSS. Conclusion: Gastric resections can be safely performed for elderly patients diagnosed with gastric cancer. This study showed that growing age is no longer a factor that will affect the clinician’s decision in performing surgery in gastric cancer patients.
Keywords: Tıp; Dahili Tıp Bilimleri; İç Hastalıkları; Geriatri; Sağlık Bilimleri; Medicine; Internal Medicine Sciences; Internal Diseases; Geriatrics; Health Sciences; Klinik Tıp (MED); Klinik Tıp; GERİATRİ ve GERONTOLOJİ; Clinical Medicine (MED); CLINICAL MEDICINE; GERIATRICS & GERONTOLOGY; Geriatri ve Gerontoloji; Geriatrics and Gerontology; Cancer; Complication; Elderly; Gastric; Surgery